求不定积分(1)dx/√x(1+√x)(2)dx/e^x+(e^-x)+2 (3)(tan^5x*sec^4x)dx(1)第一个根号包括后面的一起,(3)tan的五次方x乘以sec的四次方x

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/21 18:13:42
求不定积分(1)dx/√x(1+√x)(2)dx/e^x+(e^-x)+2 (3)(tan^5x*sec^4x)dx(1)第一个根号包括后面的一起,(3)tan的五次方x乘以sec的四次方x

求不定积分(1)dx/√x(1+√x)(2)dx/e^x+(e^-x)+2 (3)(tan^5x*sec^4x)dx(1)第一个根号包括后面的一起,(3)tan的五次方x乘以sec的四次方x
求不定积分(1)dx/√x(1+√x)(2)dx/e^x+(e^-x)+2 (3)(tan^5x*sec^4x)dx
(1)第一个根号包括后面的一起,(3)tan的五次方x乘以sec的四次方x

求不定积分(1)dx/√x(1+√x)(2)dx/e^x+(e^-x)+2 (3)(tan^5x*sec^4x)dx(1)第一个根号包括后面的一起,(3)tan的五次方x乘以sec的四次方x
说明:(2)dx/e^x+(e^-x)+2写错了吧?
正确的写法应该是dx/(e^x+(e^-x)+2).
解(1):令t=√x,则x=t²,dx=2tdt.
∴∫dx/√(x(1+√x))=2∫dt/√(1+t)
=4√(1+t)+C
=4√(1+√x)+C,(C是积分常数).
解(2):∫dx/(e^x+(e^-x)+2)=∫e^x*dx/(e^(2x)+1+2e^x)
=∫d(e^x+1)/(e^x+1)^2
=-1/(e^x+1)+C,(C是积分常数).
解(3):∫(tan^5x*sec^4x)dx=∫tan^5x*(1+tan^2x)sec^2x*dx
=∫(tan^5x+tan^7x)*d(tanx)
=(tan^6x)/6+(tan^8x)/8+C,
(C是积分常数).